Formulating and parameterizing the allocation of net primary productivity for modeling overmature stands in boreal forest ecosystems - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai (Ecological Modelling, 2006)

A Simulation of Temporal and Spatial Variations in Carbon at Landscape Level: A Case Study for Lake Abitibi Model Forest in Ontario, Canada - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Chen, Jiaxin; Parton, Sue (Mitigation and Adaptation Strategies for Global Change, 2007)

Predicting forest growth and yield in northeastern Ontario using the process-based model of TRIPLEX1.0 - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Chen, Jiaxin; Parton, Sue (Canadian Journal of Forest Research, 2005)
Process-based carbon dynamic models are rarely validated against traditional forest growth and yield data and are difficult to use as a practical tool for forest management. To bridge the gap between empirical and process-based models, a simulation using a hybrid model of TRIPLEX1.0 was performed for the forest growth and yield of the boreal forest ecosystem in the Lake Abitibi Model Forest in northeastern Ontario. The model was tested using field measurements, forest inventory data, and the normal yield table. The model simulations of tree height and diameter at breast height (DBH) showed a good agreement with measurements for black spruce (Picea mariana (Mill.) BSP), jack pine (Pinus banksiana Lamb.), and trembling aspen (Populus tremuloides Michx.). The coefficients of determination (R 2 ) between simulated values and permanent sample plot measurements were 0.92 for height and 0.95 for DBH. At the landscape scale, model predictions were compared with forest inventory data and the normal yield table. The R 2 ranged from 0.73 to 0.89 for tree height and from 0.72 to 0.85 for DBH. The simulated basal area is consistent with the normal yield table. The R 2 for basal area ranged from 0.82 to 0.96 for black spruce, jack pine, and trembling aspen for each site class. This study demonstrated the feasibility of testing the performance of the process-based carbon dynamic model using traditional forest growth and yield data and the ability of the TRIPLEX1.0 model for predicting growth and yield variables. The current work also introduces a means to test model accuracy and its prediction of forest stand variables to provide a complement to empirical growth and yield models for forest management practices, as well as for investigating climate change impacts on forest growth and yield in regions without sufficient established permanent sample plots and remote areas without suitable field measurements.

Simulating carbon exchange in Canadian Boreal forests - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Sun, Jianfeng; Wu, Haibin; Hua, Dong (Ecological Modelling, 2008)